Comparing cybersickness in virtual reality and mixed reality head-mounted displays - Kirollos, Ramy; Merchant, Wasim (Frontiers in Virtual Reality, 2023)
Defence Research and Development Canada is developing guidance on the use of Mixed Reality (MR) head-mounted displays (HMDs) for naval operations in the Royal Canadian Navy (RCN). Virtual reality (VR) HMDs display graphics to the user in 3D and completely occlude the user’s view of the real world. MR HMDs overlay and integrate graphics onto the real world allowing the user to perceive the real world and rich 3D graphic elements simultaneously. Nausea and other debilitating symptoms caused by the use of HMDs, known as ‘cybersickness’, is well documented during VR HMD exposure and can be severe. However, it is not yet clear from the literature on MR HMDs whether CS differs in VR vs. MR HMDs. The objective of this study was to determine the impact of MR HMDs on CS. This was done by modulating the quantity of graphics in two MR conditions and one VR condition. Only foreground objects were graphically rendered in the first MR condition (called ‘MR’ condition), while the entire scene was graphically rendered in the second MR condition (called ‘MR+’ condition). The ‘VR’ condition simulated the ‘MR+’ condition but was displayed in a VR HMD. Participants observed the virtually rendered scene in one of the three conditions and reported their CS with the simulator sickness questionnaire six times throughout the 30-minute experiment. We hypothesized that CS severity would increase as quantity of graphics in the display increased. Findings indicated that CS was significantly greater in the ‘MR+’ condition compared to the ‘MR’ and ‘VR’ conditions, providing partial evidence for our main hypothesis. Moreover, CS increased significantly and meaningfully after 25 minutes in the ‘MR+’ condition. These findings indicate safe use of MR HMDs by the RCN for shore-based applications provided quantity of graphics is limited.